2012
DOI: 10.1111/j.1365-2621.2012.03147.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective diffusivities and energy consumption of daylily in microwave drying

Abstract: Drying kinetics of fresh daylily flower buds (Hemerocallis Citrine Baroni cv. Mengzihua) in a microwave oven at 60, 120, 180 and 240 W, respectively, were investigated. The results indicated that, drying rate increased at the initial time (a warm-up period) and then decreased at the end time (a falling rate period) after reaching a plateau (a constant rate period). A third-order polynomial model could well describe the relationships between effective diffusivity and moisture content, and the model's coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…As the drying processed, when the material moisture content was lower than about 0.42 (g water/g solid min), a constant rate period was followed by a falling rate period which was controlled by the internal liquid diffusion. The loss of moisture content of samples caused a decrease in the absorption of microwave power and led to a descending in the drying rate [32,33]. These results were in agreement with the study of microwave drying of okra [34], coriander leaves [35], onion slices [20], and daylily flower buds [33], which indicated that a long constant rate period and falling rate period were observed after a short heating period.…”
Section: Drying Curvessupporting
confidence: 87%
“…As the drying processed, when the material moisture content was lower than about 0.42 (g water/g solid min), a constant rate period was followed by a falling rate period which was controlled by the internal liquid diffusion. The loss of moisture content of samples caused a decrease in the absorption of microwave power and led to a descending in the drying rate [32,33]. These results were in agreement with the study of microwave drying of okra [34], coriander leaves [35], onion slices [20], and daylily flower buds [33], which indicated that a long constant rate period and falling rate period were observed after a short heating period.…”
Section: Drying Curvessupporting
confidence: 87%
“…The E a of samples directly dried by AD or MD increased as the moisture content decreased (Fig. 4), similar results were obtained by Ding et al (2012). The reason was that as the free water decreased, the bond water began to evaporate, which needed more energy.…”
Section: Activation Energy (E a )supporting
confidence: 77%
“…), similar results were obtained by Ding et al . (). The reason was that as the free water decreased, the bond water began to evaporate, which needed more energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until this moment, the unique technologies used by the industry are cold storage (Landi et al, 2015), hot air convective drying, freeze-drying and other drying methods (Oberoi et al, 2007;Ding et al, 2012;Zheng et al, 2015). However, all these methods have drawbacks: cold storage is a short-term food preservation method, hot air convective drying may cause undesirable biochemical and nutritional changes in the processed product that may affect its overall quality, and freeze-drying has high productive costs.…”
Section: Introductionmentioning
confidence: 99%